The electrical and thermal effects of the input power on the needle antenna used in the treatment Hepatic tumors by microwave - S. B. Almabrok , M. M. Abulaweenat (Journal of Pure & Applied Sciences, 2020)
Microwave ablation (MWA) is a type of hyperthermia therapy, which is a process that uses heat from microwave energy to destroy cancer cells, a coaxial antenna (needle) is inserted into biological tissues, and the radiation emitted from the antenna is absorbed by the tissues and causes the cancer cells to heat up. This paper aimed to study the interaction between electromagnetic waves with tissues for treating liver cancer, and this was done by performing a two-dimensional digital simulation using the finite element method, and Maxwell’s equations and bioheat equation are used to estimate the electric field and temperature distribution in the liver tissues, and the heat is generated by the antenna to destroy the cancer cells. In addition, the effect of the input microwave power on the performance of the needle antenna was studied by analyzing the electrical and thermal effects to determine the specific absorption rate (SAR), temperature distribution in liver tissue, and the damaged portion of cancer cells during the eradication process. The obtained results showed that the absorbed power density with the distribution of temperature and the specific absorption rate is strongly affected by the input of the microwave power, and the high microwave power causes a high value of SAR and the temperature is raised above 50 C °, which may destroy cancer cells. It turns out that, at a power of 30 watts, the bulk of the tumor cells of radius (30mm) and height (80mm) were destroyed without damaging the surrounding tissues.